Pengaruh Budaya, Persepsi, dan Kepercayaan Terhadap Keputusan Pembelian Obat Tradisional di UKM Pasar Kahayan Kota Palangka Raya - Jaldi Hindratno; Meitiana Meitiana; Yoga Manurung (JEMBA : Jurnal Ekonomi Pembangunan, Manajemen dan bisnis, Akuntansi, 2021)
This study aims to determine whether there is an influence of culture, perceptions, and trust on purchasing decisions either partially or simultaneously (jointly). The research method used in this research is a descriptive-quantitative approach. The population in this study includes all consumers or customers who have purchased traditional medicinal products located on Jl.Tjilik Riwut KM.1, Kahayan Palangka Raya market, whose numbers are not yet known. The sampling technique in this study used a non-probability sampling technique with a type of accidental sampling of 80 respondents. The data collection technique used a questionnaire. The collected data were analyzed and processed with the Statistical Package for the Social Sciences (SPSS) version 24.0. The results showed that there was a significant and positive influence of culture, perceptions, and trust either partially or simultaneously on purchasing decisions for traditional medicines in the UKM Kahayan market, Palangka Raya. The suggestion given by the author in this study is that shop owners are expected to continue working in processing traditional medicine in order to increase the trust that traditional medicine is proven to heal. The government should carry out scientific testing to find out what content is in the drug, so that the BPOM and MUI labels are immediately given so that it is known to the wider community that these traditional medicines are suitable for consumption. For further researchers, they should use or add other variables such as social factors, psychological factors, and others so that they can more influence the results of purchasing decisions